Improving the Performance of Islamic Banking through Technological Innovation and Human Resource Management - Muheramtohadi, Singgih; Fataron, Zuhdan Ady (Sekolah Tinggi Ilmu Bisnis Kumala Nusa Yogyakarta, 2024)
This study base on few islamic banks those aplicate syariah law in runing their business. And the question is what the reason the principal of syaria would be executed? Which human resources those will be prepared to for running syariah bank activities? How the application of technology in assistance of bank syariah performance? The results of study are those; many syaria bank run its system not much different from commercial banks. Just change many terms in arabic language. This happen cause the commercial bank system easier and safer than syariah system. To run the syaria system, so be required better quality resources in running of businesss more than comercial banks. So, it need some analysis experts and business supervisors those more professional, to reduce the level of loses. Beside that, with the assistance of technology can help in coordination and communication with other people, especiallly between shohibul mal. Mudharib and partnership